Climate change and hunger: Responding to the challenge - Parry, Martin; Evans, Alexandra E.V.; Rosegrant, Mark W.; Wheeler, Tim (World Food Programme, 2009)
This report reviews current knowledge of the effects of climate change on hunger. It summarizes knowledge from global studies completed and provides an overview of actions that can be taken to address the challenge. We believe that unless climate change is mitigated by substantial reductions of greenhouse gases it will greatly increase hunger, especially in the poorest parts of the world. The scale of risk from climate change varies with assumptions about future development, especially future levels of poverty, but it is likely to affect tens to hundreds of millions of people. It is expected that Africa will be most affected, especially the semi-arid regions north and south of the equator. This is mainly because of projected increases in aridity resulting from climate change and because of high vulnerability consequent on low levels of income. The poorest parts of southern and south-eastern Asia are likely to be substantially affected, with strong negative impacts on agricultural production. Food production in other regions, for example Central America, may also be impacted.